High-Frequency Stimulation of Ventral CA1 Neurons Reduces Amygdala Activity and Inhibits Fear - Graham, Jalina; D’Ambra, Alexa F.; Jung, Se Jung; Teratani-Ota, Yusuke; Vishwakarma, Nina; Venkatesh, Rasika; Parigi, Abhijna; Antzoulatos, Evan G.; Fioravante, Diasynou; Wiltgen, Brian J. (Frontiers in Behavioral Neuroscience, 2021)
The hippocampus can be divided into distinct segments that make unique contributions to learning and memory. The dorsal segment supports cognitive processes like spatial learning and navigation while the ventral hippocampus regulates emotional behaviors related to fear, anxiety and reward. In the current study, we determined how pyramidal cells in ventral CA1 respond to spatial cues and aversive stimulation during a context fear conditioning task. We also examined the effects of high and low frequency stimulation of these neurons on defensive behavior. Similar to previous work in the dorsal hippocampus, we found that cells in ventral CA1 expressed high-levels of c-Fos in response to a novel spatial environment. Surprisingly, however, the number of activated neurons did not increase when the environment was paired with footshock. This was true even in the subpopulation of ventral CA1 pyramidal cells that send direct projections to the amygdala. When these cells were stimulated at high-frequencies (20-Hz) we observed feedforward inhibition of basal amygdala neurons and impaired expression of context fear. In contrast, low-frequency stimulation (4-Hz) did not inhibit principal cells in the basal amygdala and produced an increase in fear generalization. Similar results have been reported in dorsal CA1. Therefore, despite clear differences between the dorsal and ventral hippocampus, CA1 neurons in each segment appear to make similar contributions to context fear conditioning.